Single and compound logographic Kanji words elicit distinct early neurophysiological responses: ERP evidence from fluent and naïve Kanji readers. (August 2018) - Niermeyer, Madison A.; Miller, Emily; Tamaoki, Yuko; Wiggins, Eve; Stevens, Courtney
Abstract: While the N170 to printed words in alphabetic scripts is consistently left-lateralized, the available evidence on logographic scripts is much less consistent. Here, we examined the extent to which use of single-character (e.g., 目) versus compound-character (e.g., 目玉) words in a logographic script could account for differences in the laterality of early neural responses in fluent readers. Participants included both fluent Kanji readers (n = 17) as well as naïve Kanji readers (n = 19), in order to separate out differences due to low-level physical differences between stimuli. While fluent Kanji readers showed a larger amplitude N170 overall relative to naïve readers, this expertise effect was bilateral, rather than left-lateralized as is common with alphabetic scripts. Trend-level differences in laterality were observed at the earlier P1 response, which has not been extensively examined in previous studies of logographic script reading, with naïve readers only tending to show right-lateralization across both single- and compound-character Kanji words. Both participant groups differentiated single and compound Kanji words, but contrary to predictions these effects were bilateral and evident during different stages of processing in each group. Among naïve readers, compound Kanji elicited a larger amplitude P1, suggesting influence on early perceptual processing, whereas among fluent readers, these differences were not apparent until the later N170. Taken together, findings from the present study indicate that low-level visual characteristics and perceptual expertise interact during the specialization of neural circuits for print, with implications for theories of lateralization of neural circuits for print. Highlights: Fluent and naïve readers completed an ERP one-back task with Japanese Kanji words. Separate blocks used single-versus compound-character Kanji words (e.g., 目 vs 目玉). Expertise effects were bilateral at the N170, but tended to be lateralized for the P1 Word type effects were apparent on N170 for fluent readers and P1 for naïve readers. Low-level visual characteristics and expertise interact during print specialization.